Effect of nitrogen, phosphorus and potassium fertilization management on soil properties and leaf traits and yield of Sapindus mukorossi - Liu, Juntao; Wang, Dongnan; Yan, Xiaoli; Jia, Liming; Chen, Na; Liu, Jiajia; Zhao, Pengli; Zhou, Ling; Cao, Qiuli (Frontiers in Plant Science, 2024)
Rational fertilization is the main measure to improve crop yield, but there are differences in the optimal effects of nitrogen (N), phosphorus (P) and potassium (K) rationing exhibited by the same crop species in different regions and soil conditions. In order to determine the optimum fertilization ratio for high yield of Sapindus mukorossi in western Fujian to provide scientific basis. We carried out the experimental design with different ratios of N, P and K to investigate the effects of fertilization on the yield. and leaf physiology of Sapindus mukorossiand soil properties. Results showed that the yield of Sapindus mukorossi reached the highest value (1464.58 kg ha -1 ) at N2P2K2 treatment, which increased to 1056.25 kg ha -1 compared with the control. There were significant differences in the responses of soil properties and leaf physiological factors to fertilization treatments. Factor analysis showed that the integrated scores of soil factors and leaf physiological characteristic factors of Sapindus mukorossi under N2P2K2 fertilization treatment were the highest, which effectively improved the soil fertility and leaf physiological traits. The yield of Sapindus mukorossi showed a highly significant linear positive correlation with the integrated scores (r=0.70, p<0.01). Passage analysis showed that soil available nitrogen content, organic carbon content, and leaf area index were the 2 key main factors to affect the yield. RDA showed that soil organic carbon and available phosphorus were the most important factors to affect leaf physiological traits. We recommend that the optimum fertilization ratio of Sapindus mukorossi was 0.96Kg N, 0.80Kg P and 0.64Kg K per plant. Reasonable fertilization can improve soil fertility and leaf physiological traits, while excessive fertilization has negative effects on soil fertility, leaf physiology and yield. This study provides theoretical support for scientific cultivation of woody oil seed species.